The Examination of Markets of Organic Foods - Szabó, Bernadett; Gergely, Éva; Tóth, Fruzsina (Táplálkozásmarketing, 2015)
Nowadays the consumption of organic foods has an outstanding importance from the aspects of health and environmental consciousness. In this study the habits of organic food consumption in Debrecen are examined by the help of a questionnaire-based survey and a personal interview. On the basis of our results the supply of organic foods in the local markets satisfies the requirement of the consumers, and this tendency is expected to be maintained for the future. The most popular products are vegetables, fruits, dairy products, meat and honey. Generally the consumers are very satisfied with these products. Most of the buyers choose organic foods not only because these products are healthy, but for the fact that they are aware of the environmental- friendly technology by which the production happens. Consumers visiting the markets buy organic foods mainly at a weekly occasion, thus their consumption is conscious, and the healthy way of life is relevant for them. Many people do not know that there are such markets in Debrecen, in this way the promotion of these places is outstandingly important.